The communication and passing contributions of playing positions in a professional soccer team - McLean, S.; Salmon, P. M.; Gorman, A. D.; Dodd, K.; Solomon, C. (Journal of Human Kinetics, 2021)
Determining the connectivity of team members in sport provides important information on team functioning. In soccer, teams that are highly connected via passing have been shown to be more successful compared to teams less connected via passing. In addition to passing connectivity, players are connected with each other via intra-team communication (ITC) through verbal instruction, and nonverbal cues. Despite ITC being a known component of effective teamwork to enhance strategy, efficiency, motivation and concentration, ITC of individual playing positions has not previously been measured during soccer games, nor has it been associated with passing connections in a performance context. In this study, the received ITC that was perceived to be beneficial to performance during 22 competitive professional soccer matches was measured, in conjunction with the passing connections between team members. In total, 526 ITC ratings were collected and analysed, and a total of 7,693 passes were analysed. From the ITC and passing measures, a player connectivity index (PCI) representing the coupling of ITC and passing, was developed to determine the overall connectivity of the individual playing positions. Social network analysis (SNA) centrality metrics were used to determine the connectivity of the playing positions. There were significant (p < .05) main effects between playing positions for beneficial ITC, passing, and the PCI for centrality metrics, indicating that different playing positions interact with other team members differently. Pairwise comparisons indicated significant differences between individual playing positions for ITC, passing and the PCI. The two central defenders and the two central defensive midfielders had the highest mean values for ITC, passing, and the PCI compared to the other playing positions. The current findings suggest that central defenders and central defensive midfielders are positioned tactically to be highly involved in the build-up of passing moves, and to deliver beneficial task related information to team members. These findings have implications for performance analysis, coaches, and for talent identification.